2018
DOI: 10.1186/s12879-018-3069-x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity of bioactive glass S53P4 on multiresistant pathogens causing osteomyelitis and prosthetic joint infection

Abstract: BackgroundConventional local treatment for medullary osteomyelitis (OM) includes insertion of antibiotic-loaded polymethylmethacrylate (PMMA) cement. Nevertheless, PMMA may delivery irregular concentration of antibiotic to surrounding tissue. We aimed to compare the in vitro antibacterial activity of Bioactive Glass (BAG) S53P4, which is a compound showing local antibacterial activity, to that of antibiotic-loaded PMMA against multidrug resistant bacteria from OM isolates.MethodsWe studied convenience samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
(46 reference statements)
1
18
0
Order By: Relevance
“…Stress application in various forms has been shown to result in cell-size loss in the manner of SCVs in S. aureus [28]. In conclusion, BAG granules demonstrated comparable effects on biofilm to those of various nanoparticles previously described in the cited literature [19,20]. The similarity in effect of these substances may correlate to their ability to induce cellular stress.…”
Section: Platinum -S53p4supporting
confidence: 55%
See 1 more Smart Citation
“…Stress application in various forms has been shown to result in cell-size loss in the manner of SCVs in S. aureus [28]. In conclusion, BAG granules demonstrated comparable effects on biofilm to those of various nanoparticles previously described in the cited literature [19,20]. The similarity in effect of these substances may correlate to their ability to induce cellular stress.…”
Section: Platinum -S53p4supporting
confidence: 55%
“…Oxidative stress caused by BAG has been shown to inhibit fungal growth, biofilm formation as well as dimorphism of the yeast Candida albicans [19]. Growth inhibiting effects have also been detected against S. aureus and P. aeruginosa [20]. A comparable effect of ferric oxide and chitosan-coated silver nanoparticles against various bacteria, e.g.…”
Section: Platinum -S53p4mentioning
confidence: 99%
“…In that particular trial, the BG showed similar activity as calcium sulfate antibiotic beads; however, it must be noted that both groups of patients received systemic antibiotic for 6–12 weeks as part of the trial, casting doubt on the efficacy of BG as a standalone antimicrobial material [ 15 ]. In recent times, S53P4 BG garnered much attention for its antibacterial property and showed so in in vitro studies [ 51 ]. Although clinical study did not use local antibiotic when S53P4 BG was used as a bone graft substitute to treat osteomyelitis, patients received systemic antibiotic for 4 to 6 weeks postoperatively [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone reconstruction is necessary after successful infection control. Autologous bone graft is the gold standard and has osteogenic, osteoinductive, and osteoconductive properties (Ferguson et al, 2017;Calori et al, 2011;De Long et al, 2007;Egol et al, 2015). However, the volume that can be achieved is limited, and donor site morbidity is considerable (Pape et al, 2010).…”
Section: Introductionmentioning
confidence: 99%